Attitudes And Perceptions Driving Motivation And Intention To Vaccination In Pregnant Women (Survey In Penajam Paser Utara District) - Yolanda Yurian Yoseph; Sumeidi Kadarisman; Rukhiyat Syahidin (Journal on Education, 2023)
The maternal mortality rate (MMR), neonatal mortality rate (NMR) and infant mortality rate (IMR) are important indicators for assessing the quality of health services in an area. The number of MMR and IMR in Indonesia is still quite high. This study aims to examine and analyze the relationship between attitudes, perceptions, motivation and intentions to do the Covid 19 vaccine in pregnant women with the research locus in North Penajam Paser Regency. Quantitative is a research method used with the Smart PLS Structural Equation Modeling (SEM) analysis tool, 75 pregnant women were used as respondents. The results showed that attitudes and perceptions had a significant and positive effect on motivation, and motivation had a significant effect on the intention of pregnant women to be vaccinated. Attitudes and perceptions have a significant and positive effect on the intention of pregnant women to be vaccinated, both directly and indirectly.